PEMILIKAN RUMAH TINGGAL UNTUK ORANG ASING YANG BERKEDUDUKAN DI INDONESIA - RAHYENDA RAHYENDA RAHYENDRA (Jurnal Ilmu Hukum, 2020)
The Basic Agrarian Law prohibits foreigners from having property rights, the law does not close the opportunity for foreign citizens and foreign legal entities to have rights over land in Indonesia. Foreigners can have rights to land in Indonesia, that is, only with usufructuary rights, not other types. Foreigners are only allowed to own property in the form of a residential or residential unit in the form of flats (apartments), regarding the legal certainty of ownership of a residential or residential house by foreigners who are domiciled in Indonesia regulated in Government Regulation of the Republic of Indonesia Number 103 of 2015 concerning Ownership of Houses Living or Occupancy by Foreigners Domiciled in Indonesia, especially Article 2 paragraph (1) which states that foreigners can own a house for residence or residence with usufruct rights. The problems discussed in this thesis are How to Arrange and Procedure for Residential Ownership for Foreigners Domiciled in Indonesia and How the Role of Notaries in Owning Residential Foreigners Domiciled in Indonesia. The results of the study explain the Arrangement and Procedure of Residential Ownership for Foreigners Domiciled in Indonesia. Property ownership in Indonesia is currently regulated in Government Regulation Number 103 of 2015 concerning Ownership of Residential or Residential Homes by Foreigners Domiciled in Indonesia, the regulation emphasizes that foreign nationals can only exercise use rights and lease rights over property in the form of a house / occupancy. in Indonesia. The Role of Notary in Owning Residential Foreigners Domiciled in Indonesia, especially in the Jakarta area, on average do not meet the provisions stipulated by law, Notary and PPAT play a more role as someone who facilitates and makes it easier for foreigners to own land and a house to live in. Indonesia through the practice of a nominee agreement which is a legal smuggling